2014
DOI: 10.1111/cge.12427
|View full text |Cite
|
Sign up to set email alerts
|

BRCA2 gene: a candidate for clinical testing in familial colorectal cancer type X

Abstract: Familial colorectal cancer type X (FCCX) encompasses a group of families with dominant inheritance pattern of colorectal cancer (CRC) but no alteration in any known CRC susceptibility gene. Therefore, the explanation of their susceptibility is a priority to offer an accurate genetic counseling. We screened the 27 coding exons and exon-intron boundaries of BRCA2 in 48 FCCX probands. We identified 29 variants including a frameshift mutation. Deleterious variant c.3847_3848delGT p.(Val1283Lysfs*2) showed cosegreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 17 publications
5
30
0
Order By: Relevance
“…The increased risks of breast cancer with IRRs 1.5-1.7 in the age group 30-69 years and pancreatic cancer with an IRR of 2.2 after age 70 support the suggestion of disease-predisposing variants in BRCA2, causing the observed malignancies in a small subset of FCCTX families (Garre et al, 2015).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The increased risks of breast cancer with IRRs 1.5-1.7 in the age group 30-69 years and pancreatic cancer with an IRR of 2.2 after age 70 support the suggestion of disease-predisposing variants in BRCA2, causing the observed malignancies in a small subset of FCCTX families (Garre et al, 2015).…”
Section: Discussionsupporting
confidence: 57%
“…The genetic aetiology of FCCTX is most likely heterogenous and may include rare pathogenic germline variants in e.g. heterozygous MUTYH,CHEK2,BRCA2,POLE,POLD1,SEMA4A,BMPR1A,RPS20 or OGG1 or modifying single nucleotide polymorphisms in SEMA4A, EXO1, TGFBR1, or NUDT1 (Bellido et al, 2016;Dominguez-Valentin et al, 2018;Garre et al, 2011Garre et al, , 2015Hansen et al, 2015;Nieminen et al, 2011Nieminen et al, , 2014Schulz et al, 2014;Xicola et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported early-onset CRC in women with BRCA1 mutations 26 and BRCA2 mutations in families with familial colorectal cancer type X. 27 It is possible that these 13 mutations are incidental findings; however, the cancer spectrum and penetrance for many well-established and newly discovered genes will likely be redefined now that multigene panel testing is becoming more routine.…”
Section: Discussionmentioning
confidence: 99%
“…158,159 Because of the likely enrichment of heritable risk factors in FCCTX families, they have been the basis of extensive gene discovery efforts using wholegenome and exome sequencing approaches. To date, germline mutations in BMPR1A and breast cancer 2 (BRCA2) have been reported to underlie a small proportion of FCCTX 134,160 as have germline mutations in POLE or POLD1 (<2%) (Figure 1), 58,161 justifying the application of extended CRC susceptibility gene testing through multigene panels. A number of candidate CRC genes have been identified in FCCTX including semaphorin A4 (SEMA4), 162 FANCD2/FANCI-associated nuclease 1 (FAN1), 163 and ribosomal protein S20 (RPS20).…”
Section: Familial Crc Type Xmentioning
confidence: 99%